Staging memory and materiality in Eighteenth-Century theatrical biography - Boyd, Amanda Weldy (Anthem studies in theatre and performance., 2018)
Staging Memory and Materiality in Eighteenth-Century Theatrical Biography examines theatrical biography as a nascent genre in eighteenth-century England. This study specifically focuses on Thomas Davies' 1780 memoir of David Garrick as the first moment of mastery in the genre's history, the three-way war for the right to tell Charles Macklin's story at the turn of the century and James Boaden's theatrical biography spree in the 1820s and 1830s, including the lives of John Philip Kemble, Sarah Siddons, Dorothy Jordan and Elizabeth Inchbald. This project investigates the extent to which biographers envisioned themselves as artists, inheriting the anxiety of impermanence and correlating fear of competition that plagued their thespian subjects. It traces a suggestive, but not determinative, outline of generic development, noting the shifting generic features that emerge in context of a given work's predecessors. Drawing heavily on primary sources, then-contemporary reviews and archival material in the form of extra-illustrated or scrapbooked editions of the biographies, this text is invested in the ways that the increasing emphasis on materiality was designed to consolidate, but often challenged, the biographer's authority. This turn to materiality also authorized readerly participation, allowing the form of extra-illustrated or co-author biographies through the use of material insertions, asserting their own presence in the texts about beloved thespians.